PENGARUH LINGKUNGAN TERHADAP KESEHATAN MENTAL DIKALANGAN REMAJA - Adevia Putri Dinanti; Usiono Usiono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The purpose of this study was to determine the influence of the social environment, especially family, school, and peers on the intellectual development of adolescents. The focus of this study was to determine the influence of the social environment in shaping the cognitive, emotional, and social behavioral aspects of adolescents. The research method used was a literature review that analyzed the main findings of relevant studies in the fields of psychology, sociology, and education. Literature searches were conducted using platforms such as Google Scholar, Mendeley, and Garba Digital Reference (GARUDA). The results of the study showed that the family environment plays an important role in the formation of values, norms, and emotional support that affect the intellectual development of adolescents. In this case, the school environment provides opportunities for intellectual growth and social skills, but academic pressure and bullying can pose risks to adolescent mental health. The peer environment can provide emotional support and social pressure that can affect the behavior and intellectual development of adolescents. The importance of this study highlights the importance of collaboration between family, school, and peers to create a social environment that supports positive adolescent development. Integrated support from these three settings is expected to help prevent mental health problems in adolescents and provide a solid foundation as they grow up.